The use of information and communications technologies in the delivery of interprofessional education: A review of evaluation outcome levels. Issue 6 (3rd November 2015) - Curran, Vernon; Reid, Adam; Reis, Pamela; Doucet, Shelley; Price, Sheri; Alcock, Lindsay; Fitzgerald, Shari
Abstract: Interprofessional education (IPE) in health and human services educational and clinical settings has proliferated internationally. The use of information and communication technologies (ICTs) in the facilitation of interprofessional learning is also growing, yet reviews of the effectiveness of ICTs in the delivery of pre- and/or post-licensure IPE have been limited. The current study's purpose was to review the evaluation outcomes of IPE initiatives delivered using ICTs. Relevant electronic databases and journals from 1996 to 2013 were searched. Studies which evaluated the effectiveness of an IPE intervention using ICTs were included and analyzed using the Barr et al. modified Kirkpatrick educational outcomes typology. Fifty-five studies were identified and a majority reported evaluation findings at the level 1 (reaction/satisfaction). Analysis revealed that learners react favorably to the use of ICTs in the delivery of IPE, and ICT-mediated IPE can lead to positive attitudinal and knowledge change. A majority of the studies reported positive evaluation outcomes at the learner satisfaction level, with the use of web-based learning modalities. The limited number of studies at other levels of the outcomes typology and deficiencies in study designs indicate the need for more rigorous evaluation of outcomes in ICT-mediated IPE.